Genetic Analysis of TB Susceptibility Variants in Ghana Reveals Candidate Protective Loci in SORBS2 and SCL11A1 Genes - Asante-Poku, Adwoa; Morgan, Portia; Osei-Wusu, Stephen; Aboagye, Samuel Yaw; Asare, Prince; Otchere, Isaac Darko; Adadey, Samuel Mawuli; Mnika, Khuthala; Esoh, Kevin; Mawuta, Kenneth Hayibor; Arthur, Nelly; Forson, Audrey; et al. (Frontiers in Genetics, 2022)
Despite advancements made towards diagnostics, tuberculosis caused by Mycobacterium africanum (Maf) and M. tuberculosis sensu stricto (Mtb) remains a major public health issue. Human host factors are key players in tuberculosis (TB) outcomes and treatment. Research is required to probe the interplay between host- and bacterial genomes. Here, we explored the association between selected human/host genomic variants and TB disease in Ghana. Paired host genotypes datum and infecting bacteria isolate information was analyzed for associations using multinomial logistic regression. M. tuberculosis complex (MTBC) isolates were obtained from 191 TB patients and genotyped into different phylogenetic lineages by standard methods. Two hundred and thirty-five (235) non-disease participants were used as healthy controls. A selection of 29 SNPs from TB disease-associated genes with high frequency among African populations was assayed using a TaqMan® SNP Genotyping Assay and iPLEX Gold Sequenom Mass Genotyping Array. Using 26 high quality SNPs across 426 case-control samples in an association analysis we found a protective variant, rs955263, in the SORBS2 gene against both Maf and Mtb infections (PBH = 0.05; OR = 0.33; 95% CI = 0.32 – 0.34). A relatively uncommon variant, rs17235409 in the SLC11A1 gene was observed with an even stronger protective effect against Mtb infection (MAF = 0.06; PBH = 0.04; OR = 0.05; 95% CI = 0.04 – 0.05). Our findings suggest SLC11A1 and SORBS2 as a potential protective gene of substantial interest for TB, which is an important pathogen in West Africa, and highlight the need for in-depth host-pathogen studies in West Africa.